Comprehensive methodology for the integrating of the organic rankine Cycle-ORC with diesel generators in off-grid areas: Application to a Colombian case study - Ana Lisbeth Galindo Noguera; Luis Sebastian Mendoza Castellanos; Hernán Darío Pedraza-Corzo; Dimas José Rua; Electo Eduardo Silva Lora; Vladimir Rafael Melian Cobas (Cleaner Engineering and Technology)
Efficient fuel management in diesel generator sets for power generation in non-grid areas is a persistent concern. In this context, the use of an Organic Rankine Cycle (ORC) to recover heat from exhaust gases from diesel generator sets represents a promising route for additional power generation. To undertake such projects, it is necessary to understand the critical parameters related to diesel engines, including the specific fuel consumption, mass flow, and exhaust gas temperature. These parameters are fundamental to the sizing process of the ORC heat recovery system. This study introduces an innovative methodology for evaluating the operation of diesel-ORC systems based on the load demand of off-grid communities. The proposed system is a viable solution for the generation of additional power with the objective of improving the overall efficiency and meeting higher energy demands in isolated areas. Four organic fluids were selected for the ORC: R245fa, benzene, cyclopentane, and toluene. This selection was made based on many criteria, including global warming potential (GWP), ozone depletion potential (ODP), and safety classification (ASHRAE 34). In addition, the exergy behaviors of these fluids were reviewed. A comparative analysis was subsequently conducted for a non-interconnected region of Colombia to evaluate the performance of a diesel generator operating independently and in conjunction with the diesel ORC system. The key indicators employed were fuel consumption savings (L/year), energy produced (MWh/year), levelized cost of energy (LCOE, USD/kWh), and payback period (years). The results demonstrated that, over the course of a 1-year simulation period, the benzene ORC system exhibited the highest overall energy efficiency, achieving a value of 41.38%. The exergy analysis indicated that toluene had lower irreversibilities, achieving an exergy efficiency of 44.78%, followed by benzene (43.5%. Furthermore, the diesel-ORC system using benzene demonstrated a notable decrease in the specific fuel consumption from 0.282 to 0.247 L/kWh, signifying a 10.52% reduction in the annual CO2eq emissions. The cost of electricity generation decreased by 4.3%, with investment payback periods not exceeding 14 years.